"A Dissertation on Swallows" with comments on their migration by the eighteenth-century Maryland naturalist, Henry Callister. Issue 2 (October 2014) - Lawler, Ellen M.; Rubin, Sarah A.
<x xml:space="preserve">Abstract</x> In 1761, Maryland merchant and amateur naturalist, Henry Callister wrote "A Dissertation on Swallows" in response to five questions posed by a Dr Chandler. His accounts of eight Maryland species include accurate descriptions of behaviour as well as external anatomy. His brief description of the tree swallow (Tachycineta bicolor) may be one of the earliest accounts of this species. On the disappearance of swallows in winter, a topic of debate in the eighteenth century, Callister cited a number of reasons why he concluded that migration rather than hibernation was the explanation for this phenomenon. He noted differences in the habits of similar species in America and Europe and commented on the use of chimneys for nesting by chimney swifts (Chaetura pelagica), and the fact that some birds incorporated human-made fibres in their nests. These observations led him to conclude that, similar to humans, non-human species are capable of adapting to their environment, an idea remarkably advanced for his time. There is no evidence that Callister's dissertation reached its intended destination which may have been Reverend Dr Samuel Chandler, a Fellow of the Royal Society of London at that time. But this document demonstrates that Henry Callister was an enthusiastic and perceptive observer of nature and that he had the ability to use his observations to develop general concepts and a deeper understanding of the world around him.